Emergency iliac arteriotomy due to intra-arterial foreign body - Matteucci, Pablo (Cirugía del Uruguay, 1972)
The author presents a case of an extraneous body (a piece of Seldinger's catheter conductor) inside the iliac artery which was successfully re.moved surgically,. 'Ibis type of accident, though rare, is a consequence of i, odern diagnostica] methods and therapeutic techniques.